Genomic analysis and synergistic biocontrol potential of Bacillus thuringiensis MPOB Bt1 with flubendiamide against oil palm bagworm, Metisa plana walker (Lepidoptera: Psychidae) - Mohd Shawal Thakib Maidin,; Amalia Mohd Hashim,; Ahmad Zuhairi Abdul Malek,; Mohamed Mazmira Mohd. Masri,; Nurhafizhoh Zainuddin,; Raha Abdul Rahim,; Syari Jamian, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Bacillus thuringiensis MPOB Bt1 (MPOB Bt1) is a biological control agent used to suppress bagworm larvae in Malaysian oil palm plantations. Although MPOB Bt1 has been utilized in the field for biocontrol of oil palm bagworm larvae, its genetic basis for biocontrol capabilities and the combined effectiveness of MPOB Bt1 with flubendiamide have not been fully investigated. This study aimed to provide a genomic foundation for understanding the insecticidal properties of MPOB Bt1 by identifying specific genes that may be responsible for its biological activity. In addition, the study focused on evaluating the practical biological efficacy of MPOB Bt1, both alone and in combination with flubendiamide, against Metisa plana. The draft genome sequence of MPOB Bt1 was determined using Illumina HiSeq and PacBio platforms. The genome size was 6.9 Mb, with a GC content of 35.1%, and containing 5,558 coding DNA sequences, which included Cry9Ea, Cry1Ab, Cry1Ca, and Cry1Da of δ-endotoxin genes, 23 rRNAs, and 86 tRNAs. Bioassays showed that MPOB Bt1 exhibited toxicity to oil palm bagworm larvae, with an LC50 of 3.31 × 1010 spores/mL after 72 hr of treatment. The combination of MPOB Bt1 and flubendiamide showed a synergistic effect (LC50 of 1.19 × 109 spores/mL), with a ratio of experimentally observed efficacy to predicted efficacy greater than one. This study presents the draft genome sequence of MPOB Bt1 and identifies multiple insecticidal genes that potentially exhibit inhibitory effects against M. plana larvae. The toxicity and synergistic effect of MPOB Bt1 and Fbd suggest a potential strategy for controlling bagworm infestation in oil palm plantations. These findings provide a promising safer alternative to chemical insecticides for sustainable M. plana management in oil palm plantations.